Cyberloafing dan Kontrol Diri dalam Kinerja Karyawan Gen Z di Palembang - Jessica Valentsia; Ega Leovani (CV. Strata Persada Academia, 2023)
This study aims to examine the effect of cyberloafing and self-control on the performance of generation Z employees in the city of Palembang. To collect data, this study used a questionnaire distributed online via Google Form to respondents from Generation Z in the city of Palembang who were selected using the purposive sampling method where employees working using computers, laptops or cellphones connected to the internet are a requirement in determining the sample used. To test the instruments used in this study, the validity and reliability tests were carried out in this study. Before testing the hypothesis with SPSS, the researcher tested the classical assumptions first. Based on hypothesis testing, researchers found no significant relationship between cyberloafing and self-control on the performance of Generation Z employees in Palembang.